Effect Of Coenzyme Q10 On Osteoblasts Cells Number In Male Wistar Rats Gingiva Undergoing Periodontitis - Ferren Natasya Sushera; Aprilia Yuanita Anwaristi; Ikmal Hafizi; Nur Ariska Nugrahani (Jurnal EduHealth, 2023)
Inflammatory conditions in periodontitis can lead to increased production of free radicals. This study aims to determine the effect of coenzyme Q10 on the number of osteoblast cells in the gingiva of male wistar rats with periodontitis. The method used in this research is true experimental laboratory with posttest only control group design. 24 male wistar rats were divided into 4 groups, negative control group and treatment group on days 7 and 14 with each group of 6 rats. Induction of periodontitis by tying using silk ligature in the subgingival area and induced Porphyromonas gingivalis bacteria around the mandibular incisors teeth given every 2 days for 7 days. The treatment group was applied coenzyme Q10 0.1ml twice a day. 6 rats from each group were decapitated on day 7 and 14 then processed into histological preparations and then measured the number of osteoblasts. Data were analyzed using one-way ANOVA and LSD test. Conclusion: Application of coenzyme Q10 has an effect on increasing the number of osteoblast cells in the gingiva of male wistar rats with periodontitis